Convergence of telco cloud and bearer network based computing power network orchestration - Chang CAO; Shuai ZHANG; Ying LIU; Xiongyan TANG (Dianxin kexue)
Facing the combination of computing and network connection in the future network,and the development trend of computing and network integration,a computing power network orchestration model based on centralized and distributed control schemes was proposed.From the perspective of solution analysis,the computing power network orchestration scheme based on the convergence of telco cloud and bearer network can meet the future business needs of mobile edge computing (MEC) site better.With scheduling capabilities coordinated for both computing and networking,the network’s perception of services can be optimized.The specific choice of centralized or distributed control scheme is closely related to the operator’s telco cloud capabilities and the evolution stage of the bearer network.